Autochthonous starter culture selection for Salame Piemonte PGI production. (December 2022) - Franciosa, Irene; Ferrocino, Ilario; Corvaglia, Maria Rita; Giordano, Manuela; Coton, Monika; Mounier, Jérôme; Rantsiou, Kalliopi; Cocolin, Luca
Graphical abstract: Highlights: In-deep explanation of the microbiota composition of Italian dry-cured fermented sausages. Months of production (February, March, and May) showed a different microbial resource in terms of bacterial strains. Strains belonging to the same species has been differently characterized by their unique physiological capabilities. P. pentosaceus and S. xylosus selected strains improved product sensorial properties. Abstract: Salame Piemonte is a dry-fermented meat product typical of the Piedmont region in Italy, manufactured using commercial starter cultures. This study aimed to select autochthonous starter cultures (ASCs) that could be used for sausage fermentation in order to strengthen the link with the geographical area of production and improve the sensory properties of the final product. A culture-dependent approach was adopted during three different spontaneous sausage fermentation processes to isolate and characterise the main bacterial resources involved. Dominant lactic acid bacteria (LAB) in each batch were Pediococcus pentosaceus, Latilactobacillus sakei, and Latilactobacillus curvatus ; Staphylococcus xylosus was the most dominant coagulase-negative staphylococci (CNS) in all the studied batches. LAB and presumptive CNS isolates were further evaluated for their physiological properties and biotechnological potential. Thereafter, 11 strains were selected and evaluated for safety. Five selected strains (two P. pentosaceus, two L. sakei, and one S. xylosus strain) were used for pilot-scale Salame Piemonte production with seven different strain combinations. Based on the liking test, three ASC combinations led to the highest liking score compared to industrial products. These three ASCs were then used for the second pilot-scale sausage production confirming the high liking score. In summary, the use of P. pentosaceus and S. xylosus ASC significantly improved product sensory properties compared with that obtained using commercial starter cultures.